Allotropy as an Immanent Attribute of Historical Post-States - Chervinska, Olha (Sjani, 2022)
The issue of the “language of science” and terminology, which was actively regarded in terms of the “crisis of metaphysics” at the turn of the ХІХ–ХХ centuries, still remains insuf摚ciently investigated due to its immanent omnipresence. As an indicative term, the article under studies considers the so-call allotropy – the notion that was introduced into science by a mineralogist and chemist J. J. Berzelius in 1841 so as to denote different forms of the existence of homogeneous elements (for example, silicon and diamond). In humanitarian respect, the paradigm of allotropy has been actualized by the entire historical experience of the ХХ–ХХІ centuries: today, a representative of any nation may live beyond the borders of his native country, but still retain his ideological presence within the nation, thus remaining one of its “allotropic” forms. A peculiar cultural situation in post-colonial and post-Soviet world allows us today to constitute this important, although very evasive, component of historical motion in all its signi摚cance. All available examples show how ambiguous the process of formation, development, deformation or extinction of individual cultures may be, as well as what role is assigned to allotropy in such conditions. This is an emergent situation. The factor of allotropy concerns only the problem of preserving the immanent stability of a certain form, albeit with the loss of certain external features. Particular emphasis in the article has been laid on the Ukrainian context. The example of Nikolai Gogol clearly illustrates the role of allotropic forms in renewing the culture of the context that has adopted allotropy.
Keywords: Allotropy; Ukrainian literature